Management of early treated adolescents and young adults with phenylketonuria - Burton, Barbara K. (2022)
Funding Information: This work was supported by BioMarin Pharmaceutical Inc . Funding Information: The content of this manuscript was based on preparatory pre-meeting activities and presentations and discussions during two advisory board meetings that were coordinated and funded by BioMarin Pharmaceutical Inc. All authors or their institutions received funding from BioMarin to attend at least one or both meetings. Additional disclosures: BKB received consulting payments from BioMarin, Shire, Genzyme, Alexion, Horizon Therapeutics, Denali Therapeutics, JCR Pharma, Moderna, Aeglea BioTherapeutics, SIO Gene Therapies, Taysha Gene Therapy, Ultragenyx, and Inventiva Pharma, participated as clinical trial investigator for BioMarin, Shire, Denali Therapeutics, Homology Medicines, Ultragenyx, and Moderna as well as received speaker fees from BioMarin, Shire, Genzyme, and Horizon Therapeutics. AH received consulting payments from BioMarin, Chiesi, Shire, Genzyme, Amicus, and Ultragenyx, participated as clinical trial investigator for Ultragenyx as well as received speaker fees from Alexion, Amicus, BioMarin, Genzyme, Nutricia, Sobi, and Takeda. ABQ received consulting payments from BioMarin, speaker fees from BioMarin, Nutricia, Vitaflo, Sanofi, Takeda, Recordati, and travel support from Vitaflo . SEC received consulting payments and speaker fees from BioMarin as well as consulting payments from Synlogic Therapeutics. COH was clinical trial investigator for BioMarin and received consulting and speaker payments from BioMarin. SCJH received consulting payments and travel support from BioMarin and Homology Medicines. NL received consulting payments from Alnylam, Amicus, Astellas, BioMarin, BridgeBio, Chiesi, Genzyme/Sanofi, HemoShear, Horizon Therapeutics, Jaguar, Moderna, Nestle, PTC Therapeutics, Reneo, Shire, Synlogic, and Ultragenyx, participated as clinical trial investigator for Aeglea, Amicus, Astellas, BioMarin, Genzyme/Sanofi, Homology, Horizon, Moderna, Pfizer, Protalix, PTC Therapeutics, Reneo, Retrophin/Travere therapeutics, Shire, and Ultragenyx, as well as received speaker fees from Cycle Pharmaceuticals, Leadiant and Recordati. MCM II received consulting payments from BioMarin, Horizon Therapeutics, Rhythm Pharmaceuticals, Applied Therapeutics, Cycle Therapeutics, and Ultragenyx. ALSP received speaker fees from BioMarin. JCR received consulting payments from Applied Pharma Research, Merck Serono, BioMarin, Vitaflo, and Nutricia, speaker fees from Applied Pharma Research, Merck Serono, BioMarin Pharmaceutical, Vitaflo, Cambrooke, PIAM, LifeDiet, and Nutricia, as well as travel support from Applied Pharma Research, Merck Serono, BioMarin, Vitaflo, Cambrooke, PIAM, and Nutricia. SS received consulting payments, research grants, speaker fees, and travel support from BioMarin and participated as clinical trials investigator for BioMarin. ASV received consulting payments from BioMarin, Horizon Therapeutics, and Ultragenyx and participated as clinical trial investigator for Acadia, Alexion, BioMarin, Genzyme, Homology Medicines, Kaleido, Mallinckrodt, and Ultragenyx. JV received consulting payments from BioMarin, LogicBio Pharmaceuticals, Sangamo Therapeutics, Orphan Labs, Synlogic Therapeutics, Sanofi, Axcella Health, Agios Pharmaceuticals, and Applied Therapeutics as well as travel grants from BioMarin and LogicBio Pharmaceuticals. MW received consulting payments, speaker fees, and travel support from BioMarin, and participated as clinical trial investigator for Mallinckrodt, Roche, Wave, Cycle Therapeutics, and Intrabio. ACM participated in strategic advisory boards and received honoraria as a consultant and as a speaker for Merck Serono, BioMarin, Nestlé Health Science (SHS), Applied Pharma Research, Actelion, Retrophin, Censa, PTC Therapeutics, and Arla Food. Funding Information: Ideally, access to (neuro)psychological/psychiatric support should assist adolescents with identifying, understanding, and reporting of PKU-specific challenges (Table 3), offering individualized recommendations on managing these challenges. Although there is no replacement for mental health services for patients with identified needs, psychosocial support from PKU peers, e.g., through PKU camps, virtual social events, etc., can at least in the short-term help to improve metabolic control by providing individuals an opportunity to participate in supportive PKU-related educational activities potentially reducing perceived social isolation [91]. In addition to PKU camps, which may be very specific to certain regions or countries, HCPs should consider encouraging involvement in local, regional, national and international PKU patient/family advocacy and social support organizations, introducing adolescents and young adults to national/international patient registries [92,93]. Besides support from PKU peers, patients can benefit from non-PKU peer support, although some adolescents and young adults with PKU may not disclose to others and may avoid eating in with others or eating in public due to potential feelings of anxiety or feelings of being ashamed of their disease. In addition, patients with PKU of all ages, but particularly vulnerable adolescents and young adults, can benefit from having the opportunity to learn about and practice strategies that help promote feelings of empowerment and self-efficacy that can be used in both familiar and unfamiliar environments where they may experience peer pressure and feel the need to ‘fit in’. For example, a role-play approach involving behavioral rehearsal, self-monitoring, goal setting, and training in problem-solving skills with emphasis on initiation and inhibition (i.e., how to say no) could be provided by parents, PKU peers, or even members of the PKU team. These types of activities can be used to teach adolescents with PKU how to react in social situations, such as dining out, helping to avoid indulging and increased risk-taking behavior, a hallmark of the adolescent period [94].This work was supported by BioMarin Pharmaceutical Inc.The content of this manuscript was based on preparatory pre-meeting activities and presentations and discussions during two advisory board meetings that were coordinated and funded by BioMarin Pharmaceutical Inc. All authors or their institutions received funding from BioMarin to attend at least one or both meetings. Additional disclosures: BKB received consulting payments from BioMarin, Shire, Genzyme, Alexion, Horizon Therapeutics, Denali Therapeutics, JCR Pharma, Moderna, Aeglea BioTherapeutics, SIO Gene Therapies, Taysha Gene Therapy, Ultragenyx, and Inventiva Pharma, participated as clinical trial investigator for BioMarin, Shire, Denali Therapeutics, Homology Medicines, Ultragenyx, and Moderna as well as received speaker fees from BioMarin, Shire, Genzyme, and Horizon Therapeutics. AH received consulting payments from BioMarin, Chiesi, Shire, Genzyme, Amicus, and Ultragenyx, participated as clinical trial investigator for Ultragenyx as well as received speaker fees from Alexion, Amicus, BioMarin, Genzyme, Nutricia, Sobi, and Takeda. ABQ received consulting payments from BioMarin, speaker fees from BioMarin, Nutricia, Vitaflo, Sanofi, Takeda, Recordati, and travel support from Vitaflo. SEC received consulting payments and speaker fees from BioMarin as well as consulting payments from Synlogic Therapeutics. COH was clinical trial investigator for BioMarin and received consulting and speaker payments from BioMarin. SCJH received consulting payments and travel support from BioMarin and Homology Medicines. NL received consulting payments from Alnylam, Amicus, Astellas, BioMarin, BridgeBio, Chiesi, Genzyme/Sanofi, HemoShear, Horizon Therapeutics, Jaguar, Moderna, Nestle, PTC Therapeutics, Reneo, Shire, Synlogic, and Ultragenyx, participated as clinical trial investigator for Aeglea, Amicus, Astellas, BioMarin, Genzyme/Sanofi, Homology, Horizon, Moderna, Pfizer, Protalix, PTC Therapeutics, Reneo, Retrophin/Travere therapeutics, Shire, and Ultragenyx, as well as received speaker fees from Cycle Pharmaceuticals, Leadiant and Recordati. MCM II received consulting payments from BioMarin, Horizon Therapeutics, Rhythm Pharmaceuticals, Applied Therapeutics, Cycle Therapeutics, and Ultragenyx. ALSP received speaker fees from BioMarin. JCR received consulting payments from Applied Pharma Research, Merck Serono, BioMarin, Vitaflo, and Nutricia, speaker fees from Applied Pharma Research, Merck Serono, BioMarin Pharmaceutical, Vitaflo, Cambrooke, PIAM, LifeDiet, and Nutricia, as well as travel support from Applied Pharma Research, Merck Serono, BioMarin, Vitaflo, Cambrooke, PIAM, and Nutricia. SS received consulting payments, research grants, speaker fees, and travel support from BioMarin and participated as clinical trials investigator for BioMarin. ASV received consulting payments from BioMarin, Horizon Therapeutics, and Ultragenyx and participated as clinical trial investigator for Acadia, Alexion, BioMarin, Genzyme, Homology Medicines, Kaleido, Mallinckrodt, and Ultragenyx. JV received consulting payments from BioMarin, LogicBio Pharmaceuticals, Sangamo Therapeutics, Orphan Labs, Synlogic Therapeutics, Sanofi, Axcella Health, Agios Pharmaceuticals, and Applied Therapeutics as well as travel grants from BioMarin and LogicBio Pharmaceuticals. MW received consulting payments, speaker fees, and travel support from BioMarin, and participated as clinical trial investigator for Mallinckrodt, Roche, Wave, Cycle Therapeutics, and Intrabio. ACM participated in strategic advisory boards and received honoraria as a consultant and as a speaker for Merck Serono, BioMarin, Nestlé Health Science (SHS), Applied Pharma Research, Actelion, Retrophin, Censa, PTC Therapeutics, and Arla Food. Publisher Copyright: © 2022 The Authors